Effect of Nucart VG (Boswellia serrata in combination with veg glucosamine sulphate) in comparison with glucosamine sulphate to improve quality of life of knee osteoarthritis patients: a randomized controlled trial - Goni, Vijay G.; Mishra, Mukesh; Kadam, Sailee; Gandhi, Sharat S. (International Journal of Research in Orthopaedics, 2021)
Background: Boswellia serrata has been proved to be an effective and safe herb for the treatment of osteoarthritis (OA). This study aims at assessing the synergistic effect of this herb with vegetarian glucosamine sulphate, a nutritional supplement, on knee osteoarthritis using quality of life indicators. Methods: This was an open label, parallel group randomized trial of 12-week duration. Sixty-six subjects were equally randomized to two treatment arms: Boswellia serrata extract (600 mg) and glucosamine (750 mg) [Nucart VG]; and glucosamine sulphate (market comparator) 750 mg. Patients were administered 1 tablet twice-a-day post-meal for three months. Efficacy of treatment was measured on primary end-points like EuroQol-5D (EQ-5D) (health status indicator), visual analogue scale (VAS) and Western Ontario and McMaster Universities osteoarthritis index (WOMAC) scale (pain indicators), while safety was measured in terms of vital parameters. Both intention-to-treat (ITT) and per-protocol (PP) analyses were performed for comparing scores between the two groups. Results: The baseline characteristics of patients between two groups were insignificantly different (p>0.05). In ITT analysis, the health status (EQ-5D score) of patients in Nucart VG group improved significantly than the comparator group at follow up 2 (p=0.037) and showed further improvement at follow up 3 (p=0.012). The pain indicators i.e. VAS and WOMAC scores were significantly lower in Nucart VG group right from follow up 1 till follow up 3 (p<0.05). Similar were the observations during PP analysis. Conclusions: Nucart VG is beneficial for the treatment of mild to moderate knee OA, as inferred from the functional and health status assessment.